AUTHENTIC BOSNIAN GARDEN THROUGH HISTORY (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Bosnia and Herzegovina is a country with a rich cultural and historical heritage, of which the least researched is the heritage in the field of landscape architecture. The influence of the Orient on the Bosnian courtyards was very great during the rule of the Ottoman Empire, and combining their style of building gardens with the needs of the then population of Bosnia and Herzegovina, a characteristic style of gardening, called ’Bosnian flower courtyard’. The protection of Bosnian gardens as a cultural and, located at the crossroads of East and West, sublimates the influence of both cultures in its garden architecture. Spatial planning represents the cultural heritage of a nation, its identity, tradition, culture and religion. The Turkish tradition of nurturing flower courts and gardens in Bosnia and Herzegovina and some of its cities has been preserved to this day. The gardens of each country have their own specifics and are a reflection historical heritage requires a multidisciplinary approach from the aspect of analysis of a large number of factors. Bosnia and Herzegovina of tradition, culture and religion. As such garden styles must be nurtured and preserved from oblivion.